Sturgeons (Acipenseridae) from the Late Miocene of Ukraine, with a discussion of materials associated with Widhalm’s (1886) nomen nudum, †Acipenser euhuso - Hilton, Eric J.; Kovalchuk, Oleksandr; Podoplelova, Natalia (Zootaxa, 2021)
The fossil record of the family Acipenseridae (sturgeons) extends to the Late Cretaceous (c. 85 MY), with a ghost lineage extending to approximately 120 MY when the first members of the family Polyodontidae are known. Much of the fossil record of Acipenseridae is formed by isolated and fragmentary dermal bones, which bear characteristic surface ornamentation. In this paper, we report on a collection of fossil sturgeons from the Upper Miocene deposits of southern Ukraine. These specimens include those used by Widhalm to establish †Acipenser euhuso, which is a nomen nudum. While we do not establish a new taxon for these specimens, the morphological variation of those elements that are preserved does suggest the presence of several species represented in this fauna.